2012
DOI: 10.1111/ppe.12006
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Non‐syndromic Complete Atrioventricular Canal Defects

Abstract: Background Complete atrioventricular canal defects (CAVC) are a common heart defect, but few epidemiologic studies have evaluated nonsyndromic CAVC. Risk factors for nonsyndromic CAVC have not been well established. Methods To assess the relationship between risk for nonsyndromic CAVC in offspring and several sociodemographic and reproductive parental factors, including maternal diabetes and obesity, we conducted Poisson regression analyses, using data ascertained through the Texas Birth Defects Registry, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
1
22
1
1
Order By: Relevance
“…In our study, AVCD cases had female excess (59.7%) in agreement with two previous studies (Ferencz et al, : 55.7%; Hartman et al, : 52.2%); however, our result is in contradiction with a study performed by Agopian et al (), who found 48.8% affected female, the cases not deviating significantly from the sex ratio of the newborn population. There was a somewhat higher rate of multiple pregnancies (4.4% vs. 2.9%) in cases than in total livebirths in the Texas Birth Defects Registry (Agopian et al, ), the twin rate was also somewhat higher in our study (2.6% vs. 1.1%).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, AVCD cases had female excess (59.7%) in agreement with two previous studies (Ferencz et al, : 55.7%; Hartman et al, : 52.2%); however, our result is in contradiction with a study performed by Agopian et al (), who found 48.8% affected female, the cases not deviating significantly from the sex ratio of the newborn population. There was a somewhat higher rate of multiple pregnancies (4.4% vs. 2.9%) in cases than in total livebirths in the Texas Birth Defects Registry (Agopian et al, ), the twin rate was also somewhat higher in our study (2.6% vs. 1.1%).…”
Section: Discussionsupporting
confidence: 82%
“…The focus of previous studies was mainly different pathological anatomic structures, clinical manifestations, medical—primarily surgical—managements and survival of patients with AVCD (Machado et al, ; Carmi et al, ; Ferencz et al, ; Sadeghi et al, ; Digilio et al, ; Huggon et al, ; Frid et al, ; Tanner et al, ; Craig, 2006; Miller et al, ). Only three previous studies had similar objectives, however, the Baltimore‐Washington Infant Study evaluated 88 “nonchromosomal” cases including AVCD cases and AVCD combined with other CAs in unidentified multiple CAs (Ferencz et al, ), the National Birth Defects Prevention Study evaluated 302 cases with nonsyndromic AVCD and AVCD with additional major CA (Hartman et al, ) and the Texas Birth Defects Registry included 563 nonsyndromic cases but 516 cases had additional cardiac or noncardiac CAs and only 47 cases were affected with isolated AVCD (Agopian et al, ). Our study was based strictly on cases with verified isolated AVCD including only endocardial cushion defects without the presence of any other CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After exclusions, 12 studies contributed to the meta-analysis for all CHDs, 5,6,8,10,30 –37 and three to five studies contributed data to the meta-analysis for the five individual CHDs assessed (Appendix Table 1, available online; Figure 1). 5,6,810,38 …”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…4 Finally, both maternal diabetes and obesity are associated with complete atrioventricular canal defects. 5 …”
Section: Cardiovascular Conditions Of Particular Clinical Importance mentioning
confidence: 99%